Emotional intelligence and psychological well-being among a sample of academically outstanding students at King Abdul-Aziz University in Jeddah - Al-Shehri, Asayel Khaloufah; Al-Dhabiban, Nawal Abdullah (Journal of Educational and Psychological Sciences, 2022)
The study aims to identify the nature of the relationship between emotional intelligence and psychological well-being among academically superior students at King Abdul-Aziz University in Jeddah. the researcher adopted the approach The descriptive application of the study. and the study sample consisted of (210) male and female students. and the emotional intelligence scale prepared by Rasha Abdel Fattah Al-Didi (2005). and the psychological well-being scale prepared by Eman Al-Serimani (2015) was used. A statistically significant relationship between emotional intelligence and psychological well-being. there are no statistically significant differences between the average scores of academically superior students in the emotional intelligence scale and psychological well-being scale according to the variables (stage, gender, specialization, academic rate). and the study recommended the need to apply the study to another category from the categories of special education such as people with special needs in different educational stages.